1974
DOI: 10.3382/ps.0531785
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl Levels in Raw and Cooked Chicken and Chicken Broth

Abstract: Drumsticks, breast pieces, thigh meat, thigh skin, and abdominal adipose tissues from hens fed Aroclor 1254 were stewed and pressure cooked. Both cooking methods resulted in similar reductions of polychlorinated biphenyls (PCB's). Cooked chicken pieces had significantly lower PCB's than did raw pieces. Rendering of PCB's with the fat appears to be the major mode of removal.Percentage recoveries calculated from the levels of 1254 found in the cooked meat and broth, as compared to that in the raw pieces varied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Trotter et al (1989) reported PCBs were an average of 27% lower in blue fish after cooking and removal of the skin and oil drippings. In a study by Zabik (1974) that evaluated PCB levels in chicken, stewing or pressure cooking chicken pieces reduced PCBs by 50-70%, while half of the organochlorine residues transferred to the cooking media. Zabik (1984) reviewed early studies on the effect of cooking/processing on residue levels in meat, fish, and poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Trotter et al (1989) reported PCBs were an average of 27% lower in blue fish after cooking and removal of the skin and oil drippings. In a study by Zabik (1974) that evaluated PCB levels in chicken, stewing or pressure cooking chicken pieces reduced PCBs by 50-70%, while half of the organochlorine residues transferred to the cooking media. Zabik (1984) reviewed early studies on the effect of cooking/processing on residue levels in meat, fish, and poultry.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the loss found for the high-fat ciscowets, minimal losses of PCBs were found from carp harvested from Saginaw Bay, Lake Huron (Zabik et al, 1982). Somewhat higher losses of PCBs have been found for stewing or pressure cooking of chickens (Zabik, 1974) as well as roating of turkey rolls (Zabik, 1990), but both of these studies used considerably longer cooking times than is appropriate for cooking crab.…”
Section: Resultsmentioning
confidence: 98%
“…In a study by Zabik (1974) that evaluated PCB levels in chicken, stewing or pressure cooking chicken pieces reduced PCBs by 50-70%, while half of the organochlorine residue transferred to the cooking media. This may result in residues contaminating foods such as rice or pasta cooked in this type of broth (Funk et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Condensation has shown to be effective in the reduction of telodrin in milk (2), freeze-drying significantly reduced lindane, dieldrin, p,p'-DDT, and o,p'-DDT-DDD from whole eggs (3), heating skimmed milk decreased PCB residues (4), and spray-drying promoted losses of chlorinated hydrocarbon pesticides (5,6). Cooking has reduced these lipophylic compounds from such products as poultry (7)(8)(9)(10)(11), sausage patties (12), bacon (13), pork loins (14), pork muscles (15) and beef loaves with texturized soy (16). Most of the losses were attributed to fat rendering or leaching out during cooking-the more severe the rendering the greater the loss.…”
Section: Introductionmentioning
confidence: 99%